2021
DOI: 10.21203/rs.3.rs-250219/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence of Urogenital Schistosomiasis and Water, Sanitation and Hygiene Risk factors for transmission among Primary School Children in an urban endemic area of Kinondoni Municipality in Dar es Salaam, Tanzania

Abstract: Objectives: To determine the prevalence of urogenital schistosomiasis and water, sanitation, and hygiene risk factors for transmission among primary school children in an urban endemic area of Kinondoni Municipality in Dar es Salaam, Tanzania. Methods: A quantitative cross-sectional study was conducted between June and August 2020 to determine the prevalence of S.haematobium. A total of 250 urine samples were collected from primary school children, examined for haematuria using urinalysis test strips, and S.ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
2
0
0
Order By: Relevance
“…The factors which were predictive of infection in this study were sex of the child, years of residency, school location, practices towards urogenital schistosomiasis, and urinating in the water body. This observation conforms to several studies reported in Sub-Saharan Africa [ 34 , 35 , 38 40 ]. Of the factors mentioned above, only years of residency remained a significant predictor of urogenital schistosomiasis transmission in the multivariate logistic regression analysis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The factors which were predictive of infection in this study were sex of the child, years of residency, school location, practices towards urogenital schistosomiasis, and urinating in the water body. This observation conforms to several studies reported in Sub-Saharan Africa [ 34 , 35 , 38 40 ]. Of the factors mentioned above, only years of residency remained a significant predictor of urogenital schistosomiasis transmission in the multivariate logistic regression analysis.…”
Section: Discussionsupporting
confidence: 93%
“…Hence, stimulating unhygienic practices perpetuating the transmission of the diseases that’s why children with unhygienic practices such as open urination in water sources and the habit of walking barefooted were highly infected compared to the rest. The findings are comparable with the previous studies done in Tanzania, Sudan, Nigeria, Senegal [ 34 37 ].…”
Section: Discussionsupporting
confidence: 91%